2017
DOI: 10.1111/geb.12574
|View full text |Cite
|
Sign up to set email alerts
|

Modelling native and alien vascular plant species richness: At which scales is geodiversity most relevant?

Abstract: Aim: To explore the scale dependence of relationships between novel measures of geodiversity and species richness of both native and alien vascular plants.Location: Great Britain.Time period: Data collected 1995-2015.Major taxa: Vascular plants. Methods:We calculated the species richness of terrestrial native and alien vascular plants (6,932 species in total) across the island of Great Britain at grain sizes of 1 km 2 (n 5 219,964) and 100 km 2 (n 5 2,121) and regional extents of 25-250 km diameter, centred ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
118
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(127 citation statements)
references
References 64 publications
6
118
1
2
Order By: Relevance
“…It should also be noted that EGV set 5 included data of three different categories (i.e., topographic, climatic, land use), showing the importance of considering explanatory variables that can potentially provide complementary information [23,47,49,102,105,143]. Moreover, this also shows that land use data, while directly associated with the human action on the landscape, can have a decisive effect on the distribution patterns of native and invasive species [23,24,67,[144][145][146].…”
Section: Discussionmentioning
confidence: 95%
“…It should also be noted that EGV set 5 included data of three different categories (i.e., topographic, climatic, land use), showing the importance of considering explanatory variables that can potentially provide complementary information [23,47,49,102,105,143]. Moreover, this also shows that land use data, while directly associated with the human action on the landscape, can have a decisive effect on the distribution patterns of native and invasive species [23,24,67,[144][145][146].…”
Section: Discussionmentioning
confidence: 95%
“…Bailey et al. () found that while automatically extracted landform data added the most explanatory power to species richness models (smallest study unit 1‐km 2 ); hydrological and material‐based (soil, geology, superficial deposits) geofeatures were also significant. Their results emphasize the importance of analysing distinct landforms in biodiversity modelling.…”
Section: Introductionmentioning
confidence: 99%
“…Geodiversity as a discipline is increasingly being included in the assessment and management of natural and cultural environments (ZwoliƄski et al 2017). It is also being used as an instrument to value ecosystems and its services and to explain biodiversity distribution (Hjort et al 2015, Bailey et al 2017, Tukiainen et al 2017). However, in most geodiversity studies, temporal aspects of geodiversity are underrepresented.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, (com-ponents of) geodiversity have been used to explain the distribution of biodiversity resulting from landscape patterns (Hjort et al 2015, Bailey et al 2017.…”
Section: Introductionmentioning
confidence: 99%